Synergistic Effect of APP and TBC Fire-Retardants on the Physico-Mechanical Properties of Strandboard - Tian, Feiyu; Xu, Deliang; Xu, Xinwu (Materials, 2022)
This study explored the feasibility of fabricating fire-retardant strandboard with low mechanical properties deterioration to the physico-mechanical properties. A hybrid fire-retardant system of ammonium polyphosphate (APP) and 1,3,5-tris(2,3-dibromopropyl)-1,3,5-triazinane-2,4,6-trione (TBC) was investigated. Thermogravimetric analysis results show that both APP and TBC enhance the thermal stability and incombustibility of wood strands. An infrared spectrum was applied to investigate the effect of flame retardants on the curing behaviors of polymeric diphenylmethane diisocyanate (PMDI) resin. Based on the results of limiting oxygen index (LOI) and Cone calorimetry (CONE), APP and TBC both lead to a higher fire retardancy to strandboard. It is worth mentioning that the two flame retardants lead to evidently differential influences on the modulus of rupture (MOR), modulus of elasticity (MOE), internal bond (IB), and water-soaking thickness swelling (TS) properties of strandboard. Hence, a hybrid flame retardant is prominent in manufacturing strandboard with both good fire retardant and satisfying physico-mechanical properties.